Determinan Kesejahteraan Mayarakat di Indonesia - Khairudin Khairudin; Aminah Aminah (Akuisisi: Jurnal Akuntansi, 2022)
Welfare for the people will soon be realized if it is supported by sufficient resources and good management.The purpose of this research is to examine the effect of government size and fiscal decentralization on the welfare of all provincial governments in Indonesia for the 2014-2018 period. Welfare is measured by HDI; the size of the local government is measured using the total revenue earned in a year; and fiscal decentralization is measured through profit sharing funds, general allocation funds, and special allocation funds obtained in a year. The test was conducted through panel data regression with the findings that the size of the government and fiscal decentralization had a positive and significant effect on welfare. This finding is show of the importance of the sustainability of stakeholder theory and the joint commitment of all parties to maximize the performance of local governments in terms of local revenue and decentralization funds to speed up the realization of welfare for the community